Influence of torrefaction with Mg-based additives on the pyrolysis of cotton stalk. (August 2018) - Zeng, Kuo; Yang, Qing; Zhang, Yang; Mei, Yanyang; Wang, Xianhua; Yang, Haiping; Shao, Jingai; Li, Jiashuo; Chen, Hanping
Highlights: Mg-based additives strengthened deoxygenation and served as catalyst in pyrolysis. Torrefaction with Mg-based additives significantly increased aromatic hydrocarbons. A maximum aromatic hydrocarbons yield of 16.05% was obtained with MgO-K2 CO3 . The optimal torrefaction condition was: mass ratio 0.5:1 and temperature 320 °C. MgO-K2 CO3 increased H2 yield from 1.39 to 3.67 mmol/g with torrefaction severity. Abstract: The study presented an approach to introduce Mg-based additives into cotton stalk for strengthening deoxygenation effect during torrefaction. Then catalytic pyrolysis of torrefied feedstock with Mg-based additives residue as catalyst was performed at 550 °C for 10 min in a fixed-bed reactor. The effects of torrefaction temperature (200, 230, 260, 290, 320, 350 °C), type of Mg-based additive (MgO and MgO-K2 CO3 ), mass ratio of additive to biomass (0.5, 1 and 2) on pyrolysis were investigated. The results indicated that yields of bio-char and bio-oil significantly increased and decreased with torrefaction temperature rising to 350 °C. MgO inhibited pyrolysis bio-char yield increase with torrefaction severity. MgO-K2 CO3 increased H2 yield a lot from 1.39 to 3.67 mmol/g. It also effectively improved the aromatic hydrocarbons in bio-oil and the reduction of acids. A maximum aromatic hydrocarbons yield of 16.05% was obtained with MgO-K2 CO3 (the mass ratio of 0.5:1) at torrefaction temperature of 320 °C.